Evaluación de la formación de agregados en emulsiones de perfluorocarbono en interacción con sangre y expansores plasmáticos (2017)
"Our group has been working on developing a perfluorocarbon emulsion (PFCE) to restore the lost blood volume and oxygen carrying capacity in case of hemorrhagic shock. One of the problems with these emulsions is the formation of aggregates. The aim of this study is to determine is the components that generate aggregation when the PFCE are in touch with blood and plasma expanders." -- Tomado del Formato de Documento de Grado.